Systematics and evolution of droseraceae - Fleischmann, A.; Cross, Adam; Gibson, R.; Gonella, P.; Dixon, Kingsley (2018)
The Droseraceae belongs to the botanical order Nepenthales and comprises three genera: Drosera (sundews) with adhesive traps; and the sister genera Dionaea (Venus’ flytrap) and Aldrovanda (waterwheel plant), each of which evolved snap-traps. Vegetative and generative morphology of each genus are illustrated and interpreted based on phylogenetic evidence. Phylogeny, evolutionary history, and infrageneric classification of Drosera are discussed in light of molecular phylogenetic data, and illustrated with phylogenetic trees and maps of their distribution.